If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 + -5x = 8 + -7x Solving 24 + -5x = 8 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 24 + -5x + 7x = 8 + -7x + 7x Combine like terms: -5x + 7x = 2x 24 + 2x = 8 + -7x + 7x Combine like terms: -7x + 7x = 0 24 + 2x = 8 + 0 24 + 2x = 8 Add '-24' to each side of the equation. 24 + -24 + 2x = 8 + -24 Combine like terms: 24 + -24 = 0 0 + 2x = 8 + -24 2x = 8 + -24 Combine like terms: 8 + -24 = -16 2x = -16 Divide each side by '2'. x = -8 Simplifying x = -8
| 2k^2-15=k | | 8y+4=8y+4 | | 7n^2-40=-51n | | -5x^2+9x+12=2x-6x^2 | | x^2+(-3)+(-8)=0 | | 3n-14=58 | | 8-(4n+7)=17 | | k^2+20=4 | | v^2+13v-3=-3+6v | | 28.66=6g+3.52 | | 4x+6+2x=14 | | 4-x=2x-13 | | n^2+4n-6=6 | | 88x+613=624 | | 5x+5=140-x | | -x^2+41x=400 | | (4x+1)(x+6)=0 | | m^2=7m-6 | | -3(3p+3)-2(6-11p)=3(6+4p) | | 3(w-1)=2w | | X^7=9 | | 7y+5+y=43 | | -4(x-4)=(2-1) | | f(x)=-2-1 | | k^2=14k-48 | | 11=7+(1-x) | | 3x-4=10x+7 | | 7x-(5x+5)=3x-47 | | 20+5x-4x=-6x+2 | | 4x+6x+3+9=5x+5+4x | | 4-2x=8-5x+5 | | (6x-1)(5x+4)=0 |